Educational Magazine Contains Phytochemical Screening Materials for Chemistry Education Students: Development and Validation - Furnapasta, Lestia; Sofia, Baiq Fara Dwirani (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to develop and validate an educational magazine as supplementary reading material for chemistry education students, focusing on the phytochemical screening of renggak leaf extracts using methanol and ethanol as solvents. The development of this magazine was carried out using a 4D model which was carried out until the third stage. The three stages are Define, Design, and Develop. Validation was conducted by three experts, and the evaluation results, analyzed using the Aiken V formula, yielded a score of 0.86, categorized as highly valid. Practicality testing with students indicated a score of 88%, demonstrating that the magazine is effective and user-friendly as a learning medium. Thus, this magazine is a viable supplementary resource for chemistry education students, particularly in understanding secondary metabolite compounds and phytochemical screening. The novelty of this research lies in the development of a visual educational magazine based on the phytochemical screening of Amomum dealbatum leaves, which has not been previously presented in this format to support chemistry learning.